Seminar Parenting Di TK Dharma Wanita Unhas - Fitri, Riskal; Mimin, Rasmiati; Rusli, Nurintan; Qonita, Nadia Muna; Endang, Endang; Nurhafsah, Siti (Universitas Pejuang Republik Indonesia, 2025)
The parenting seminar at Dharma Wanita Kindergarten UNHAS aims to improve parents' understanding and skills in supporting early childhood development. This seminar provides a place or forum for discussion and sharing experiences, introducing effective educational methods, increasing parental involvement in education and parenting, providing information related to the idea of playing together between parents and children, and sharing tips and experiences between students and parents. Through this seminar, it is hoped that parents can create an environment that supports children's growth and development optimally, is more familiar with children's needs and abilities, and is able to better facilitate children's development.